Reuse of low sulfur oil residues as a base for boiler and marine fuel - E. R. Zvereva; A. O. Makarova; Yu. V. Bakhtiyarova; V. I. Korolev; N. P. Ilyin; A. N. Turanov; O. S. Zueva (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. A complex of various physico-chemical methods has been studied to explore the possibilities of reuse of oil residues (oil sludge) of low-sulfur high-paraffin oil deposits of the Mangyshlak peninsula (Kazakhstan) as a promising raw material for boiler and marine fuel with improved operational and environmental characteristics.METHODS. Determination of the conditional viscosity of oil sludge (in degrees Engler, ° E) was carried out using an Engler viscometer VU-M-PCP according to GOST 6258-85 «Petroleum products. The method of determining the conditional viscosity». Studies of the lowest working heat of combustion of oil sludge were carried out using an adiabatic bomb calorimeter ABK-1B (Russia) according to GOST 21261-91 "Petroleum products. Method for determining the highest heat of combustion and calculation of the lowest heat of combustion". Determination of the mass fraction of sulfur in the studied oil sludge was also carried out using an adiabatic bomb calorimeter ABK-1B (Russia) according to GOST 3877-88 «Petroleum products. Method of determination of sulfur by burning in a calorimetric bomb». To analyze the results obtained, data obtained using the nuclear magnetic resonance method were used. Proton NMR spectra were recorded on a Bruker AVANCE III NMR spectrometer operating at a frequency of 600.13 MHz for 1H and equipped with a highresolution inverse sensor for three cores (TXI, 5 mm). Data processing and analysis were performed using Bruker Topspin 3.6.1.RESULTS. It is shown that in terms of heat of combustion and viscosity properties at temperatures above 50 oC, this oil sludge is similar to boiler fuel oil M100. It was found that the use of carbonate sludge of chemical water treatment at a concentration of 0.1 wt. % allows you to further reduce the viscosity by 5-6% and reduce the sulfur content in the combustion products, without reducing the lower working heat of combustion of the oil product. The complex nature of the relationship between the width of NMR lines and viscous properties has been revealed, which may indicate the existence of associates of highmolecular paraffins even in slightly viscous liquid petroleum products. The nature and characteristic sizes of the resulting associates are discussed. It is shown that the addition of medium-distillate diesel fractions will make it possible to obtain a better fuel option for marine engines, gas turbine and boiler installations with a reduced amount of resinous-asphaltene substances, reduced viscosity values and solidification temperatures, high heat of combustion and low sulfur content.СONCLUSION. The conducted complex of physico-chemical studies has shown the possibility of using low-sulfur Mangyshlak oil sludge as a basis for obtaining fuel for marine engines, gas turbine and boiler plants, steam boilers and industrial furnaces.